2020
DOI: 10.1080/20008198.2020.1824398
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and posttraumatic stress: examining emotion dysregulation as a mediator in an African American community sample

Abstract: Background : African Americans experience more severe and chronic posttraumatic stress disorder (PTSD) symptoms compared to other racial groups, and thus it is important to examine factors that are relevant for the aetiology of PTSD in this population. Although racial discrimination has been implicated as an exacerbating factor in the development and maintenance of PTSD, relatively less is known about mechanisms through which this process may occur. Objective : The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
6
13
0
Order By: Relevance
“…The current study examined the role of race and discrimination frequency in PTSD, depression, and substance use problems among a racially diverse, primarily low-income sample of women who presented to the ED for a SAMFE and were assigned to an intervention, active control, or TAU and followed up over a six-month period. Consistent with recent work suggesting that racial discrimination is associated with PTSD (Bird et al, 2021; Mekawi et al, 2020; Sibrava et al, 2019), findings revealed positive associations between the frequency of discrimination experiences and both PTSD and depression symptoms six months postrape after controlling for race, intervention condition, and other significant demographics. Contrary to our study hypotheses and to the self-medication model of substance abuse (Khantzian, 1997), discrimination frequency was not associated with alcohol or drug problems in the current sample.…”
Section: Discussionsupporting
confidence: 85%
“…The current study examined the role of race and discrimination frequency in PTSD, depression, and substance use problems among a racially diverse, primarily low-income sample of women who presented to the ED for a SAMFE and were assigned to an intervention, active control, or TAU and followed up over a six-month period. Consistent with recent work suggesting that racial discrimination is associated with PTSD (Bird et al, 2021; Mekawi et al, 2020; Sibrava et al, 2019), findings revealed positive associations between the frequency of discrimination experiences and both PTSD and depression symptoms six months postrape after controlling for race, intervention condition, and other significant demographics. Contrary to our study hypotheses and to the self-medication model of substance abuse (Khantzian, 1997), discrimination frequency was not associated with alcohol or drug problems in the current sample.…”
Section: Discussionsupporting
confidence: 85%
“…In the validation study, the EDS scores were significantly associated with all the subscales of the DERS, and the EDS demonstrated incremental validity over the DERS in predicting different psychopathology conditions (e.g., substance abuse symptoms, post-traumatic stress symptoms, borderline pathology, depressive symptoms, and number of suicide attempts) [ 18 ]. Other studies have supported the use of the EDS in a variety of clinical populations [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This notion is supported by a recent study showing that experiences of racialized bias or discrimination affect emotional dysregulation. 36 We also note some recent studies indicating a genetic contribution to anhedonia 37 , 38 through this assessment were outside the scope of this analysis.…”
Section: Discussionmentioning
confidence: 85%